1997
DOI: 10.2307/5925
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Interactions between Species of Seaweed Fly

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Animal Ecology. Summary 1. This paper describes the colonization p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…In contrast, studies showing interspecific facilitation in organisms of similar sizes are very rare, particularly in animals (Bertness & Yeh 1994, Lively & Raimondi 1987, Hodge & Arthur 1997. In the case of salt marsh plants living under hypersaline conditions, interspecific facilitation between seedlings occurred when salt tolerant species reduced substrate salinity, which in turn allowed salt intolerant but competitively superior species to survive (Bertness & Yeh 1994).…”
Section: Coexistence In Similar-sized Sessile Organismsmentioning
confidence: 81%
“…In contrast, studies showing interspecific facilitation in organisms of similar sizes are very rare, particularly in animals (Bertness & Yeh 1994, Lively & Raimondi 1987, Hodge & Arthur 1997. In the case of salt marsh plants living under hypersaline conditions, interspecific facilitation between seedlings occurred when salt tolerant species reduced substrate salinity, which in turn allowed salt intolerant but competitively superior species to survive (Bertness & Yeh 1994).…”
Section: Coexistence In Similar-sized Sessile Organismsmentioning
confidence: 81%
“…Phillips et al (1995) reported that seaweed £ies, Coelopa frigida and C. pilipes, can interact either as competitors or as amensalists; in addition, the direction of the amensalism depends upon environmental conditions. Hodge & Arthur (1997) described how according to the resource presented to these £y populations the interaction can either be (+, 7) or (0, 7).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated a significant change in the abundance and biomass of Coleoptera, dipteran adults and larvae on wrack over time (Inglis 1989;Chown 1996;Hodge & Arthur 1997;Catenazzi & Donnelly 2007;Garrido et al 2008). However, these studies investigated only dipteran or coleopteran assemblages (Chown 1996;Hodge & Arthur 1997;Garrido et al 2008), or the sampling method included the collection of meiofauna and associated larval stages (Inglis 1989;Catenazzi & Donnelly 2007) that were too small to be retained on 1-mm mesh sieves (Inglis 1989;Chown 1996). In this study, the biomass of Diptera differed significantly between sampling days, with highest biomass occurring during later stages.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, in a study on dipteran assemblages on the north-east coast of England, adult abundance peaked at the beginning and end of the wrack cycle, with the adults found during later stages being the offspring of those that originally colonised the fresh wrack (Hodge & Arthur 1997).…”
Section: Discussionmentioning
confidence: 99%